“We have made it on the journey, but we have not yet arrived”: the right to education for learners with barriers to learning and disabilities through an inclusive lens - Thaisi, Mapitso (Department of Public Law, 2024)
Since 1994, there has been changes in education policies in South Africa and the push for more inclusive learning environments. Policies such as the White Paper 6 were developed to accommodate learners with disabilities and those with barriers to learning within mainstream education. However the link between policy and implementation is often blurred, especially in the instance of learners with disabilities attending mainstream schools. Many of these learners slip through the cracks of the education system without the necessary support and even drop out of schools in the absence efficient methods of identifying, assessing, referring and proving learners with the appropriate support. This research explored how two ordinary primary schools in Cape Town where assessing and providing support for learners with barriers to learning. Using a qualitative research method, the research chose the Metro Central Education District in Cape Town as the case for this study and conducted interviews with school teachers, occupational therapists and school based support staff members from an affluent school and a school from a low socio-economic area. The research found that schools did not have clear policies and guidelines in place to identify learners with barriers to learning. Furthermore, the findings revealed differences between the two schools and indicated that the school based in the affluent area had more support in place, while the school based in the poorer community, had less support in place. Thus, context shapes the type of support which schools can afford and ultimately how learners enjoy their rights to an education. The Department of Education needs to implement strategies that facilitate urgent implementation of inclusive education policies in schools.